Climatological Aspects in the Circulation of Sustainable Apartment - Sihombing, Reza Phalevi (Universitas Pendidikan Indonesia, 2019)
Population density and depletion of land for buildings are one of the main reasons for the construction of vertical housing in this modern era. Apartment building is one of the vertical buildings which is suitable to accommodate many occupants to solve land problems, but the apartment also provides many major problems, especially in the surrounding natural environment. Therefore sustainable architectural design that is contextual to the environment is one solution to solve the problem. Jakarta is one of the cities with high intensity of apartment building growth. This paper will explain the architectural design process for sustainable apartments in Pluit, North Jakarta, Indonesia based on a climatological approach.Keywords— Apartment, Climatologist, Sustainable